International Monetary Fund Annual Report 2016. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2016)
The year was marked by difficult challenges and milestone achievements. To reinvigorate modest growth at a time of uncertainty about a complicated global economy, the IMF membership endorsed a three-pronged approach of monetary, fiscal, and structural policies to get the world economy back on a stronger and safer growth track. Highlights of the IMF's work during the year included entry into effect of its quota and governance reforms approved in 2010, which increase the Fund's core resources and make it more representative of the membership; commitments for increased financial support, policy advice, expertise, and training to help low-income developing countries achieve the U.N. Sustainable Development Goals; analysis of the international monetary system; inclusion of the Chinese currency in the basket of currencies that make up the Special Drawing Right; and policy advice on the economic repercussions of mass migration of refugees from Syria and other conflict-afflicted states. The IMF Annual Report, which covers the period May 1, 2015 to April 30, 2016, discusses all of these issues, plus a wide range of policy matters that the Executive Board addressed during the year.